Nutritional status of soil-transmitted helminthiasis-infected and uninfected children - Nelly Simarmata; Tiangsa Sembiring; Muhammad Ali (Indonesian Pediatric Society, 2015)
Background Soil-transmitted helminth (STH) infections remain a public health problem in developing countries. Their prevalence is particularly high in rural areas with people of low socioeconomic level. A single or mixed STH infection rarely causes death, but can affect nutritional status, growth, cognitive development and human health, especially in children.Objective To compare the nutritional status of STH-infected and uninfected children.Methods This cross-sectional study was conducted in June 2010 in children from 3 primary schools in the Simpang Empat and Kabanjahe Subdistricts, Karo District, North Sumatera Province. Fecal examinations were done by the Kato-Katz method to diagnose STH infections. Participants of this study consisted of 140 infected children and 141 uninfected children. Nutritional status classification was based on the 2000 Centers for Disease Control growth charts. All categorical data were analyzed by Chi-square test.Results Of 140 infected children, 8.6% were infected with Ascaris lumbricoides, 17.1% with Trichuris trichiura and 74.3% with mixed infections (Ascaris lumbricoides and Trichuris trichiura). We found significantly more STH infected children with mild to moderate malnutrition than the uninfected group. We also found significantly more mildly to moderately malnourished children with moderate infection intensity than mild infection intensity.Conclusion We find significantly more STH infected children with mild to moderate malnutrition than the uninfected group. We also find significantly more mildly to moderately malnourished children with moderate infection intensity than mild infection intensity. Higher severity of infection is associated with lower nutritional status.